Beyond Exams: Alternative Assessment Methods for Holistic Student Evaluation - Ristiliana, Ristiliana; Husniati, Lisanul; Zaki, Amir (CV Berkah Syahdin Trust, 2025)
Conventional exam-focused evaluation systems are becoming less effective in assessing the diverse skills needed in modern education. According to the OECD’s 2023 findings, 72% of teachers agree that standardized tests fall short in evaluating essential abilities like critical thinking, creativity, and teamwork. As workplace needs and student diversity grow, there is a pressing demand for assessment reforms that reflect real-world challenges and cater to different learning styles. This research investigates the efficacy of alternative evaluation approaches in measuring comprehensive student growth, comparing their influence on academic results, motivation, and skill development with traditional testing. Using a mixed-methods approach, the study analyzed 150 peer-reviewed articles (2018–2023) from Scopus and ERIC, along with case studies from 20 institutions in 10 countries employing portfolios, project-based evaluations, and peer reviews. Results showed that alternative methods improved skill retention by 35% (p<0.01), with project-based assessments closely linked to real-world competence (r=0.68). Portfolios boosted engagement by 42%, while peer feedback strengthened metacognitive skills. Successful implementation relied on clear rubrics (β=0.57) and teacher training (β=0.49). The study concludes that holistic assessments surpass traditional exams in fostering key competencies, emphasizing the need for teacher development and systemic support.